(untitled) (Bioresearch Communications, 2026)
The Hippo signaling pathway plays an important role in human diseases. This pathway takes part in the initiation, development and metastasis of various types of cancers, including lung cancer. The effector molecules of this pathway, Yes-associated protein 1 (YAP), Tafazzin (TAZ), undergo constant regulation. In the cytoplasm, YAP/TAZ are degraded in multiple ways, the ubiquitin-dependent degradation being the most prominent one. Ubiquitin specific proteases 21 (USP21) and YOD1 are two of the many deubiquitinating enzymes that participate in the regulation of ubiquitination on YAP/TAZ. Although the roles of USP21 and YOD1 vary from disease to disease, they have a tumor suppressing role in lung cancer. These two enzymes also interact to stabilize each other and show a synergistic effect in inhibiting cell proliferation in lung cancer. Therefore, this study was designed to predict which set of isoforms of USP21 and YOD1 shows stable interactions and how it could affect lung cancer. Using a number of in silico techniques such as protein structure prediction, structure validation, docking analysis and molecular dynamics simulation studies, it was identified that the USP21 isoform b and YOD1 isoform 1 show the most stable interaction. Thus, it was predicted that these set of isoforms would exhibit better suppression of lung cancer. Bioresearch Commu. 12(2): 2174-2192, 2026 (January)